Veiled intentions: Hamas’s strategic deception and intelligence success on 7 October 2023 - Muhanad Seloom (21875261) (2025)
On 7 October 2023, Hamas dealt a severe blow to Israel’s deterrence by launching a multi-front incursion that killed more than a thousand Israelis and captured hundreds. Prevailing commentary frames the attack as an Israeli intelligence debacle; this study instead interrogates Hamas’s intelligence success. Drawing on strategic deception, the intelligence-cycle model and asymmetric warfare scholarship, it analyses how a resource-starved non-state actor concealed intentions. Process-traced evidence from investigative reporting, declassified Israeli documents, and interviews the author conducted with Hamas’s leadership, members and analysts reveals four enabling pillars: meticulous operational security, systematic open-source and cyber intelligence collection (OSINT), insider human intelligence (HUMINT) and a professionalised intelligence apparatus shaped by decades of counter-espionage practice and external tutoring. The findings underscore adversary agency and expose the fragility of technological superiority for advanced militaries. Other Information Published in: Intelligence and National Security License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/02684527.2025.2576903